Endocrine Effects of Repeated Hot Thermal Stress and Cold Water Immersion in Young Adult Men. Issue 2 (April 2021) - Podstawski, Robert; Borysławski, Krzysztof; Pomianowski, Andrzej; Krystkiewicz, Wioletta; Żurek, Piotr
The aim of the study was to determine the effect of repeated hot thermal stress and cold water immersion on the endocrine system of young adult men with moderate and high levels of physical activity (PA). The research was conducted on 30 men aged 19–26 years (mean: 22.67 ± 2.02) who attended four sauna sessions of 12 min each (temperature: 90−91°C; relative humidity: 14–16 %). Each sauna session was followed by a 6-min cool-down break during which the participants were immersed in cold water (10−11°C) for 1 min. Testosterone (TES), cortisol (COR), dehydroepiandrosterone sulfate (DHEA-S), and prolactin (PRL) levels were measured before and after the sauna bath. The participants' PA levels were evaluated using the International Physical Activity Questionnaire. Serum COR levels decreased significantly ( p < .001) from 13.61 to 9.67 µg/ml during 72 min of sauna treatment. No significant changes ( p >.05) were noted in the concentrations of the remaining hormones: TES increased from 4.04 to 4.24 ng/ml, DHEA-S decreased from 357.5 to 356.82 µg/ml, and PRL decreased from 14.50 to 13.71 ng/ml. After sauna, a greater decrease in COR concentrations was observed in males with higher baseline COR levels, whereas only a minor decrease was noted in participants with very low baseline COR values ( r =−0.673, p <.001). Repeated use of Finnish sauna induces a significant decrease in COR concentrations, but does not cause significant changes in TES, DHEA-S, or PRL levels. Testosterone concentrations were higher in men characterized by higher levels of PA, both before and after the sauna bath.